On Efficiency and Stability in Two-way Flow Network with Small Decay: A Note - Banchongsan Charoensook (Fondazione Eni Enrico Mattei (FEEM), 2022)
Most literature in strategic network formation shows that there is a substantial tension between stability and efficiency. In this note, I show that such is not the case in the twoway flow model with small decay studied by Bala and Goyal (2000a) and De Jaegher and Kamphorst (2015). Specifically, I show that every link receiver in a Nash network serves as an efficient trans-mitter of information. I also generalize this result to the case of player hetero-geneity and then provide a fine-detail characterization of effiicient networks.
Keywords: C72; D85; 330; Network Formation; Nash Network; Two-way Flow Network; Agent Heterogeneity; Efficient Network